Preparation and Reactions of (1H-Tetrazol-5-yl)zinc Pivalates - Tüllmann, Carl Phillip; Steiner, Sebastian; Knochel, Paul (Synthesis, 2020)
The preparation and reactivity of new solid heterocyclic organozinc reagents, namely N-protected (1H-tetrazol-5-yl)zinc pivalates, as storable solids with appreciably air and moisture stability are reported. They are obtained in high yields from protected 1H-tetrazoles by deprotonation using the mixed zinc–magnesium base TMPZnCl·Mg(OPiv)2 (abbreviated as TMPZnOPiv; TMP = 2,2,6,6-tetramethylpiperidyl). Subsequent cross-couplings and copper-catalyzed electrophilic aminations using hydroxylamine benzoates give access to functionalized 1H-tetrazoles while tolerating many functional groups.
Keywords: zinc; tetrazole; cross-coupling; amination; organozinc pivalates